Les affaissements miniers dans le bassin ferrifère lorrain : quand le territoire re-politise la gestion du risque - François Duchêne (Développement Durable et Territoires)
With the end of mining activity and the sale of miners’ dwellings, the question of subsidence, hitherto an industrial hazard, became an environmental risk. The damage caused by mining, an issue previously addressed privately by the owners, became the responsibility of government services when mining concessions were handed over to the State. The handover was particularly delicate in the iron-ore basin of Lorraine, where the closeness of the ore to the surface made this area more liable to subsidence than others. Local reactions to the phenomenon were all the more heated as the territory was already in the throes of an economic crisis. The solutions sought by State services to safeguard against risk were primarily technical and sector-specific. However, it was not just houses that were ‘moved’ by the subsidence. It likewise provoked a reaction from local stakeholders who, with a political, economic and social heritage rooted in mining and the steel industry, had been bruised and battered by deindustrialisation. In the end, it was, in fact, due to a specific, territorial context, involving the mobilisation of social forces still deeply influenced by recent history, that the management and treatment of these risks took on a political dimension.